The call of the minaret - Cragg, Kenneth (Oneworld, 2003)
First published in 1956, this text remains one of the most acclaimed works in the field of Muslim-Christian relations. Now the author brings the discussion into the 21st century in this third edition of his seminal work, complete with new material including an updated bibliography. Taking the Muslim call to prayer as his starting point, the author unravels the significance of the muezzin's haunting cry, considering prophethood, prayer, politics and community to present a more complete understanding of Islam. It becomes clear that the Islamic call to prayer transcends the boundaries of religion, containing a summons for Christians and Muslims alike. Drawing upon both scholarship and his own abiding spirituality, Kenneth Cragg's study of the two faiths pays homage to both, drawing them out of the shadows of enmity and into the light of mutual understanding.